Online and In-Person Learning in Islamic Higher Education: A Comparative Study of Character Formation Using the Islamic Character Formation Ecology Model - Taufikin Taufikin; Ahmad Falah; Habib Badawi; Moses Adeleke Adeoye (IJECA (International Journal of Education and Curriculum Application), 2026)
This study stems from concerns that digital transformation in higher education may weaken the moral and spiritual dimensions, particularly in Islamic education, which places character development at its core. This research aims to compare the impact of online and face-to-face learning on students’ character development and to explain the underlying pedagogical mechanisms. The study employs a mixed-methods approach with an explanatory sequential design. Quantitative data were collected via a survey of 240 Islamic Religious Education students, using a Likert scale to measure akhlak, tazkiyah, and adab. Qualitative data were obtained through semi-structured interviews and observations. Quantitative analysis employed an independent-samples t-test and Cohen’s d, while qualitative data were analyzed thematically. The results revealed significant differences across all character dimensions, with face-to-face learning consistently outperforming online learning. The largest differences were observed in the spiritual dimension, followed by moral and social-relational dimensions, indicating that the deeper the character dimension, the more it depends on the quality of the learning environment. Theoretically, this study proposes the Islamic Character Formation Ecology (ICFE) model, which views character as the result of interactions among pedagogical relationships, a spiritual atmosphere, and practical discipline. This model shifts the approach to character development from an individual-centered to an ecological-relational one. In practical terms, these findings underscore the importance of redesigning digital learning to ensure that character development remains intact.